Cake monitoring system using Internet of Thing (IoT) for small and medium enterprises (SMEs) - Danial, Muhammad Imran; Masek, Alias (Penerbit UTHM, 2020)
The aim of this project is to develop a cake monitoring prototype system. In this regard, the small and medium-sized industries (SMEs) of the cake and bakery sector have had most of the problems when it comes to monitoring and handling cakes in the chiller. Without monitoring system, it is difficult to maintain the temperature, humidity and good expiry date to ensure the quality of a cake for customers. This study develops a prototype for the cake monitoring system to resolve the problems. The Design Thinking model was utilized to frame the development process. The prototype uses the NodeMcu ESP8266, NodeMcu base, sensor DHT 11, and software aided design by using AutoCad 2018, Fritzing, Blynk Application and MIT App Inventor. The testing showed that, if the temperature reached 29oC or the humidity decreased from 70% and if the expiry date was reaching 14 days; a notification will be sent to owner’s handphone. With that, this prototype is reliable to help the owner’s cake and bakery shops to maintain the' quality of the cakes.